Hubungan Rasa dan Waktu Penyajian Makanan Serta Sisa Makanan Lunak pada Pasien RSUD Dr.R.Koesma Tuban - Miranda Febbin Ariefah; Dwi Kurnia Purnama Sari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
The purpose of this study was to determine the relationship between taste and time of food serving with food waste in patients at RSUD. R. Koesma Tuban. Leftover food is often considered an indicator of patient dissatisfaction with the quality of the food provided. However, this study attempts to see further whether there is a significant relationship between these variables. A quantitative approach was used with a survey method and observation of a number of patients who received soft food. A questionnaire was used to measure the level of satisfaction with the taste and timeliness of food serving, while direct observation was carried out to record the leftover food. The sample of this study was 133 people and was conducted in June 2024 at RSUD dr. R. Koesma Tuban. The results of the Spearman correlation test showed a value of ρ = 0.374, which means there is no significant relationship between the taste of food and leftover food. The results of the Spearman correlation test showed a value of ρ = 0.634. This means that there is no significant relationship between the timeliness of food delivery and leftover food. Although most patients were satisfied with the taste and time of delivery, this did not consistently affect the amount of food left over. In conclusion, other factors besides taste and timeliness of provision may play a more important role in determining food waste at RSUD dr. R. Koesma Tuban, therefore further research is needed to identify these factors.